BCN ceramics with excellent electromagnetic wave–absorbing property derived from high‐yield and soluble precursor polymers. (25th August 2020) - Zhang, Shuai; Long, Xin; Ji, Xiaoyu; Shao, Changwei
Abstract : Polymer‐derived ceramics have been used as functional nanocomposites with designable structures and tunable properties. In this report, three types of BCN ceramics were fabricated from boron‐modified precursors, which were in turn synthesized by the polymerization of decaborane as boron‐rich monomer with diamines as linkages. All of these precursors present high ceramic yield and good solubility in N, N ‐dimethylformamide and dimethyl sulfoxide. The composition and structure of precursors were characterized using elemental analysis, Fourier‐transform infrared, gel permeation chromatography, and nuclear magnetic resonance. The structural evolution during the polymer‐to‐ceramic process and the microstructure of pyrolyzed BCN ceramics were analyzed in detail. The BCN ceramic with 16 wt. % carbon content derived from alkyldiamines exhibited promising X‐band absorption properties. When the sample thickness is only 1.8 mm, the minimum reflection loss reaches −40.9 dB at 15.8 GHz with an effective absorption bandwidth of 5.3 GHz. The simple and processable method for BCN ceramics was developed to satisfy the demand of materials with adjustable electromagnetic wave absorption properties. Abstract : BCN ceramics derived from polymers have excellent electromagnetic wave absorption performance in X‐band with ultrathin thickness (1.8 mm), wide effective absorption bandwidth (5.3 GHz), and strong absorption ability (RLmin =–40.9 dB).